A litigância climática estratégica como potencial instrumento de proteção à Amazônia brasileira - Oliveira, Letícia Fernandes de (2023)
The climate issue is one of this century’s wicked problems because it represents a risk to humanity’s existence. For this reason, the Judiciary is urged to decide more frequently on matters related to this issue, through the proliferation of the so called climate litigation. On the other hand, climate change has a close re lation with other environmental crises currently faced/caused by the human kind . The devastation of the Amazon Region biomes is an example of those relations, since the natural sciences had already demonstrated how this destruction contributes to climate change at the same time it may be accelerated by the natural cycles’ instability caused by them. In this context, noticing the relevance of exploring all the possible ways of minimizing the ant h ropic al action in the nature, we sought to explore the use of strategic climate litigation as an auxiliary mechanism in the preservation of the Amazon Region in Brazil given the urgency o n avoiding the increasing of the devas ta tion and on reverting the damages before the region ecosystem reaches the inflexion point expecting to find a receptive scenary in the Brazilian jurisdction for those cases . The scientific bases of the importance of protecting the Amazonian biomes for maintaining cli mate balance were initially investigated, to justify a climate litigation approach aimed at the preservation of these biomes, verifying the existence of multiple studies that attest to these elationships. It was then noticed that the strategies already de veloped by litigants in other jurisdictions around the world where climate action already has a successful track record presented interesting possibilities for how to bring the Amazon issue to these disputes. Finally, from Brazilian scenario analysis, we n oticed a vast and diverse normative, as well as evidence of a receptive judiciary to the debates to be brought by th ese actions. We concluded, after all, that strategic climate litigation approach directed to the mainten an ce of the Amazonian biomes is a go od opportunity to develop and expand actions to combat climate change in Brazil while preserving the region that contains the largest tropical forest of the world.